Opportunities and Challenges for Limitation of Plastic Waste in Balikpapan City - Khaerani, Thalita Rifda; Sarai, Melsy Vanesa (Budapest International Research and Critics University, 2021)
The Balikpapan City Government has made various efforts to reduce the volume of single-use plastic use. This study aims to examine various opportunities and challenges faced by the Balikpapan City Government in an effort to limit waste, especially single-use plastic waste. This type of research uses descriptive qualitative research with purposive informant selection techniques, data collection techniques in the form of observation, in-depth interviews, documentation and literature studies along with data analysis techniques using triangulation methods. The results of the study show that in the implementation of the policy of limiting single-use waste, there are internal opportunities and external opportunities in addition, resulting in factors that become internal challenges and external challenges. The recommendations given are for regencies/cities that have not issued a policy on banning single-use plastic products/packaging, it is recommended to make local regulations, then efforts are needed to improve supervision in order to minimize elements who still ignore existing regional regulations.